Patterns of daily prayer in Second Temple period Judaism - Penner, Jeremy (Studies on the texts of the desert of Judah, 2012)
1.1. Preliminary Remarks on the Anthropology of Sleep in the Ancient World2. The Influence of Cosmology on Prayer; 3. Prayers for Protection; 3.1. Ps-Philo, L.A.B. 60:1-3; 3.2. Jub. 12:16-27; 3.3. 11Q11 V; 3.4. 4Q510-511: Were Prayers for Protection Routinized?; 4. Nocturnal Praise; 4.1. 4Q503; 4.2. 1QHa XXV 30-33; 5. 4Q334: A Liturgy for Praise or Protection?; 5.1. Genre and Setting; 6. Conclusions; Conclusions; Bibliography; Index of Ancient Sources.